Indirect Flux-Oriented Control of Faulty Single-Phase Induction Motors - M. Jannati; N. R. N. Idris; M. J. A. Aziz (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Most types of electrical machines such as Induction Motors (IMs) can be modeled by an equivalent 2-phase machine (d-q model). For instance a single-phase IM with two main and auxiliary windings can be modeled as an equivalent 2-phase IM. Also a faulty single-phase IM (single-phase IM under open-phase fault) can be modeled as an unbalanced 2-phase IM. This study confirms this concept by modeling a single-phase IM with one of its stator phases, open. In addition the study shows that the vector control of this faulty IM can be performed by some modifications in the vector control of healthy IM (the proposed vector control in this paper is based on Indirect Flux-Oriented Control (IFOC)). MATLAB simulation results show the good performance of the proposed technique.